A Hybrid Multidimensional Performance Measurement Model Using the MSD-MPSI-RAWEC Model for Turkish Banks - Yüksel Aydın; Osman Yavuz Akbulut (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractThe purpose of the paper is to analyze the multidimensional sustainability performance of deposit banks that operate in the Turkish banking industry. For this aim, the current research presents a novel hybrid decision-making model comprising of MSD, MPSI and RAWEC methodologies. In the developed decision-making model, the MSD and the MPSI objective weighting methods are utilized to assign significance weights to the criteria, while the RAWEC, a relatively new technique, is employed for banks' ranking. In order to check the robustness of the recommended model, various sensitivity and benchmark analyses were conducted. According to the findings of the study, the most important criterion in determining the sustainability performance of deposit banks is the total hours spent on employee training. Moreover, the most successful bank in terms of multidimensional sustainability is Garanti BBVA. Furthermore, sensitivity and comparison analyses prove that the integrated framework in this study is a powerful, reliable and useful decision tool that can be utilized in assessing the sustainability performance of banks. Besides, practical and managerial implications based on the findings of the applied decision-making tool are discussed.